ROLE OF REPRODUCTIVE HORMONES IN SCHIZOPHRENIA - CHITRA Y. DHUME; SUNANDA AMONKAR; MITCHELLE MENEZES (International Journal of Pharma and Bio Sciences, 2013)
Schizophrenia is a clinical syndrome of variable, but profoundly disruptive psychopathology that involves cognition, emotion, perception and other aspects of behaviour. It ranks among the top ten causes of disability in developed countries worldwide. Gonadal hormones have recently been implicated in the psychopathology, sex differences in onset, prognosis and treatment of schizophrenia. The present study investigated the effects of serum levels of testosterone, follicle stimulating hormone, luteinizing hormone and prolactin in a group of sixty patients. The study was conducted over a period of 18 months in the Goa Medical College and the Institute of Psychiatry and Human Behaviour. Diagnosis of Schizophrenia was made using the ICD-10 classification. A control group of sixty healthy subjects was recruited. As compared to matched controls, the acutely admitted patients suffering from Schizophrenia exhibited significantly low serum levels of the reproductive hormones suggesting a possible role for hormones in the psychopathology of the disease.